2018
DOI: 10.35568/earlychildhood.v2i2b.291
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Permainan Tradisonal Cak Bur Terhadap Peningkatan Interaksi Sosial Siswa Taman Kanak-Kanak

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui efektifitas permainan cak bur terhadap peningkatan interaksi sosial siswa taman kanak-kanak di kota Padang. Penelitian ini melibatkan 37 orang siswa sebagai subjek penelitian, dimana 18 orang masuk dalam kelompok eksperimen dan 19 orang lainnya masuk dalam kelompok kontrol, pemilihan subjek penelitian dan penempatannya kedalam kelompok eksperimen dan kontrol dilakukan secara acak. Desain penelitian ini adalah pretest postest group control. Pengumpulan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…The significant difference can be seen from the initial pre-test data for both the control and experimental groups, which were in the not-good category. After the treatment in the experimental group, there was an increase in the results of the post-test, which showed that the mutual cooperation character was getting stronger as they were in the very good category, whereas in the control group, when the post-test was carried out, the results showed that the mutual cooperation character was in the sufficient category (Aulia, 2018;Marlina & Pransiska, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…The significant difference can be seen from the initial pre-test data for both the control and experimental groups, which were in the not-good category. After the treatment in the experimental group, there was an increase in the results of the post-test, which showed that the mutual cooperation character was getting stronger as they were in the very good category, whereas in the control group, when the post-test was carried out, the results showed that the mutual cooperation character was in the sufficient category (Aulia, 2018;Marlina & Pransiska, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Apart from that, learning activities place more emphasis on cultivating religious, independent, mutual cooperation and creative character values. The application of games is also very effective in improving social interaction skills in kindergarten students (Aulia, 2018;Ulhusna & Diana, 2020). This is because through play, children are able to develop the ability to build relationships, collaborate, practice social maturity with peers and lay the foundation for practicing socialization skills, practicing roles with more mature people or the community.…”
Section: Discussionmentioning
confidence: 99%
“…Keempat, penelitian yang dilakukan oleh Aulia (2018), bahwa hasil analisis data yang diperoleh di dalam penelitian ini bahwa permainan cakbur sangat efektif dalam meningkatkan interaksi sosial anak dengan teman sebayanya di Taman Kanak-Kanak. Permainan Cak bur ini dapat membantu anak untuk mengembangkan kerjasamanya, mengembangkan penyesuaian diri, menciptakan interaksi yang positif dengan temannya, mampu mengkondisikan anak untuk mengontrol dirinya, menumbuhan sikap empati dan mentaati aturan dalam bermain serta menghargai orang lain.…”
Section: Hasil Dan Pembahasanunclassified